Antioxidative properties of roselle (Hibiscus sabdariffa L.) in linoleic acid model system - Tee, Pau‐Ling; Yusof, Salmah; Mohamed, Suhaila (Emerald, 2002)
A study was conducted to determine the antioxidative properties of roselle (Hibiscus sabdariffa L.) methanol extract by monitoring the formation of dieneconjugated compounds and thiobarbituric acid reactive substances (TBARS) in linoleic acid model system. The properties were compared to those of butylated hydroxyanisole (BHA) and αtocopherol. Results indicated that the roselle extract showed stronger antioxidant properties than BHA or αtocopherol. A total of 200 parts per million (ppm) of the extract inhibited more than 85 per cent of dieneconjugated compounds after seven days of incubation at 40○C. The total phenolic compound was found to be 2.96mg/g calyx as gallic acid equivalent. This indicates that roselle is a good source of natural antioxidants which may protect the body from damage by free radicals and lipid peroxidation. The protective effect is probably through the action of highly bioavailable ascorbic acid, βcarotene and phenolic compounds, especially the anthocyanins.